As Thick as Thieves: Exploring Thomas Hobbes' Critique of Ancient Friendship and its Contemporary Relevance. (February 2019) - Slomp, Gabriella
Recent decades have witnessed a revival of interest in ancient friendship both as a normative and as an explanatory concept. The literature concurs in holding Hobbes responsible for the marginalisation of friendship in political science and suggests that Hobbes devalued friendship because of his understanding of man. This article argues that although Hobbes' appraisal of friendship hinges on his assumption that man is self-interested, his critique of normative friendship does not rest on that notion. Hobbes' challenge to us is this: without foundation in the 'truth' (i.e. the 'Good Life') that underpinned ancient friendship, modern friendship, whether self-interested or selfless, cannot be assumed to be a civic virtue, nor an index of the health of a political association, nor a facilitator of domestic or global peace. Hobbes' critique is especially relevant for writers who maintain that a resurgence of friendship can nurture concord and foster reconciliation within contemporary liberal democracies.